Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.38126/jspg180204
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Nature-Based Solutions into Climate Adaptation Policy and Planning in Bangladesh

Abstract: Bangladesh is regarded as one of the most climate-vulnerable regions in South Asia due to its unique geographical location and socio-economic conditions. Natural disasters, changing temperatures, precipitation, and sea level rise have affected agricultural production, infrastructure, and livelihoods in the country. To face these challenges, nature-based solutions (NbS) can address climate change adaptation, protection and management of natural ecosystems, and biodiversity conservation. For example, in Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Por último, se recomienda la implementación de siete SbN, y de acuerdo con los adelantos en este tema en la Unión Europea, se propone el diseño de políticas ambientales que contengan SbN, aunque a diferencia de la UE, y teniendo en cuenta el estado financiero del país, se deben tener en cuenta soluciones que sean económicamente asequibles, e ir actualizando el marco de las políticas, así como lo expresado por Islam et al (2021), sobre cómo se fueron incluyendo proyectos ambientales en políticas de Bangladesh, hasta llegar al Eight Five Year Plan (8FYP), primer documento político en donde se mencionan las SbN.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por último, se recomienda la implementación de siete SbN, y de acuerdo con los adelantos en este tema en la Unión Europea, se propone el diseño de políticas ambientales que contengan SbN, aunque a diferencia de la UE, y teniendo en cuenta el estado financiero del país, se deben tener en cuenta soluciones que sean económicamente asequibles, e ir actualizando el marco de las políticas, así como lo expresado por Islam et al (2021), sobre cómo se fueron incluyendo proyectos ambientales en políticas de Bangladesh, hasta llegar al Eight Five Year Plan (8FYP), primer documento político en donde se mencionan las SbN.…”
Section: Discussionunclassified
“…Ubicándonos en el sur de Asia encontramos a Bangladesh, considerado uno de los países asiáticos más vulnerables al clima, lo que ha incentivado al gobierno de este país a diseñar políticas en miras a la adaptación al cambio climático y el desarrollo sostenible. Entre estas políticas se encuentra el Eight Five Year Plan (8FYP), publicado en el 2020, en el que se enfatiza el desarrollo y gestión de los recursos hídricos en Chittagong Hill Tracts, que incluye la creación de cinturones verdes y estructuras ecológicas para el manejo de la erosión y restaurar y proteger los ecosistemas relacionados con el agua; el 8FYP fue el primer documento político de Bangladesh donde se mencionan las SbN, aunque este número de políticas ambientales nacen del Seventh Five Year Plan (7FYP) en el 2015 (Islam et al, 2021). La evolución de estas políticas ambientales se observa en la figura 4.…”
Section: Prosiguiendo Con Los Antecedentes La Investigación Environme...unclassified
“…Similarly, a systematic analysis of twenty policy documents in the development, climate and environment sectors found that although only one used NbS terminology, there was a growing emphasis on the protection and management of natural ecosystems using concepts such as ecosystem-based adaptation, ecosystem services, and green building (Islam et al, 2021). Nevertheless, there was a lack of implementation guidelines, financial support and mechanisms for monitoring and evaluating NbS initiatives, and a need for greater inter-ministry cooperation; national funding support; a national promotional campaign; more evidence-based research and capacity-building; and greater involvement of youth, marginalized people, and women.…”
Section: Scaling Up High Quality Nature-based Solutions In Bangladeshmentioning
confidence: 99%
“…Both natural and managed ecosystems are being degraded due to climate change, pollution and over-exploitation of resources, posing an increasing threat to livelihoods, especially for the rural poor (Rasul and Thapa, 2004;Miah et al, 2010;Abdullah-Al-Mamun et al, 2017). NbS offer the potential to reverse this degradation and boost climate resilience, whilst empowering local communities and enabling sustainable development, but they are not well integrated into national policies (Islam et al, 2021), partly due to lack of awareness of their benefits (Huq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%